Diversity of Fungi Associated with Taxus baccata Linn. in Different Seasons - Sharma, Ankush; Sagar, Anand; Joshi, Madhavi (Indian Forester, 2017)
Studies conducted to find the fungal species associated with plant tissues and rhizosphere samples of Taxus baccata Linn. (Taxaceae) during summer, rainy and winter seasons in Himachal Pradesh. Study revealed the presence of twelve rhizospheric fungal species belonging to 8 genera (Aspergillus, Epicoccum, Fusarium, Mortierella, Mucor, Penicillium, Rhizopus and Trichoderma). A total twelve species of endophytic fungi were isolated from various plant parts (viz. root, stem, needles and bark). These species belonged to 10 genera (Absidia, Alternaria, Aspergillus, Chaetomium, Epicoccum, Fusarium, Penicillium, Phoma, Rhizopus and Trichoderma). A total of forty species of AM fungi belonging to 6 genera (Acaulospora, Endogone, Entrophospora, Gigaspora, Glomus and Sclerocystis)were isolated from the mycorrhizosphere of T. baccata. Fungal colonization in roots revealed the presence of fungal hyphae and vesicles in them.